RANCANG BANGUN SISTEM INFORMASI biMBA AIUEO SOCCER SCHOOL - Reza Setiawan; Ahmad Khotib; Rouli Doharma (STMIK Widuri Jakarta, 2024)
Along with the development of advances in information technology at this time, which makes human life easier in terms of carrying out daily activities. biMBA AIUEO is an agency that implements and socializes the biMBA paradigm and the biMBA method and is a place where parents can guide their children in order to foster children's interest in reading. Bimba AIUEO also founded a soccer team, namely the Bimba Soccer School. The problem in the Bimba Soccer School is that the data processing in the Bimba Soccer School is still manual, to find out some information about this soccer school can only be done by visiting the training location directly, hearing word of mouth and through brochures or pamphlets. just. Therefore, from observations that have been made of a lack of knowledge about information about the BiMBA AIUEO Soccer School, a design was made for the creation of a Website-Based BiMBA AIUEO Soccer School Information System. The purpose of this research is to analyze, design, and create an information system for the AIUEO Soccer School biMBA. The system was developed using the waterfall model system development life cycle (SDLC) method, using the PHP programming language, MySQL database design. The results of the study show that the application built is useful for admins, parents and the general public as an information medium in gathering information about BiMBA Soccer School more accurately and more easily because it can be accessed anywhere because it is web-based computerized.